2009
DOI: 10.1002/app.31544
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a hindered amine stabilizer on optical and mechanical properties of poly(methyl methacrylate) exposed to gamma irradiation

Abstract: The ability of Tinuvin 622, a Hindered Amine Stabilizer (HAS), in decreasing of radiation damage to commercial PMMA matrix used in manufacturing of medical supplies was examined. Effects of gamma irradiation in PMMA specimens irradiated at dose range of 10-60 kGy were assessed by comparison of the variation of viscosity average molar mass (M v ) of PMMA with Tinuvin 622 (PMMA-622) when compared with PMMA without the additive (PMMA-control). Samples containing Tinuvin 622 presented smaller decrease of M v as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…This result does mean that the scission effect is predominant in the PMMA matrix. Similar results were data for PMMA exposed to gamma irradiation 7,21,40 .…”
Section: Viscosity Measurements For Pmma Solutionssupporting
confidence: 88%
See 2 more Smart Citations
“…This result does mean that the scission effect is predominant in the PMMA matrix. Similar results were data for PMMA exposed to gamma irradiation 7,21,40 .…”
Section: Viscosity Measurements For Pmma Solutionssupporting
confidence: 88%
“…Besides studying the molar mass of polymers exposed to gamma rays, viscosity analysis provides critical data about the interactions of additives and polymer molecules in solution 21,40 . In this investigation, viscometry parameters of methyl-ethyl-ketone solutions of Poly (methyl methacrylate) and its mixture with commercial additives were obtained by single concentration determinations.…”
Section: Viscometry Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…After 63 days of storage at 30 kGy dose, the yellowness index measured was 2.78 and 0.17 to PMMA-control and PMMA-622, respectively. These results showed that the Tinuvin 622 is a good alternative for stabilizing the PMMA against gamma irradiation damage in sterilization processes with low cost (Aquino et al, 2010) The scheme in Figure 13 is generally accepted to explain the aspects of the chemistry mechanism of HALS action to inhibit polymer photo-oxidation. This scheme was used to guide a strategy to assess Tinuvin 622 action in radiolytic stabilization of PMMA (Aquino & Araujo, 2008).…”
Section: Action Of Stabilizers In Polymeric Medical Device Exposed Tomentioning
confidence: 91%
“…Thus the nitroxyl radicals could regenerate many times through the chain reaction before their depletion. The single Electron Spin Resonance (ESR) spectrum was obtained for Tinuvin 622 sample irradiated at 100 kGy and was attributed to nitroxyl radical (Aquino et al, 2010). The chemistry of HALS had been widely documented for UV irradiation.…”
Section: Action Of Stabilizers In Polymeric Medical Device Exposed Tomentioning
confidence: 99%